Review on Pharmacovigilance Practice for Safety of Medication System in Bangladesh (Bangladesh Pharmaceutical Journal, 2017)
Pharmacovigilance is a system that provides safety to the patients in case of medication. It mainly deals with adverse drug reactions. With the outbreak of new diseases new medicines are developing worldwide. So to ensure the safety of drug, pharmacovigilance is very necessary. National pharmacovigilance center of a country coordinates the overall activity of pharmacovigilance in collaboration with international regulatory authorities like WHO, the Uppsala Monitoring Centre etc. Integration of pharmacovigilance system in public health has positive impact on improvement of health care system. In Bangladesh Directorate General of Drug Administration (DGDA) is playing an active role to ensure the safety of medication system.Bangladesh Pharmaceutical Journal 20(1): 105-114, 2017